Flexible Wearable Chemoresistive Ethylene Gas-Monitoring Device Utilizing Pd/Ti3C2Tx Nanocomposites for In Situ Nondestructive Monitoring of Kiwifruit Ripeness - Guo, Laizhao; Chu, Shaojie; Li, Yun; Huang, Wentao; Wang, Xiang (ACS applied materials & interfaces, 2024)
Kiwifruit, renowned for its antioxidant properties and nutritional richness, faces challenges in maintaining quality during transportation, often leading to suboptimal products reaching the market. To address this issue, a wireless transmission flexible ethylene monitoring device (WFEMD) was developed. This device comprises a flexible ethylene gas sensor and a signal transmission processing unit integrated with electronic components, enabling real-time monitoring capabilities. In this study, the catalytic activity of Pd and Pd/Ti heterojunctions was leveraged to enhance the ethylene gas sensing. The impact of Ti3C2Tx modified with varying masses of Pd nanoparticles on ethylene gas response levels was investigated. The signal transmission processing unit, fabricated by using the laser direct-writing method, was optimized to collect signals from the flexible ethylene gas sensor, convert them into corresponding ethylene concentrations, and transmit data via an antenna. By introducing a random forest (RF) classification algorithm, a remarkable 97.5% accuracy in predicting kiwifruit ripeness grades was achieved. The algorithm facilitated precise classification by collecting key parameters such as ethylene and CO2 during transportation. The WFEMD enables real-time acquisition of kiwifruit ethylene gas information, which is transmitted wirelessly for data visualization and traceability via mobile terminals. This empowers managers with timely insights into ethylene emissions and ripeness predictions, facilitating informed decision-making processes.Kiwifruit, renowned for its antioxidant properties and nutritional richness, faces challenges in maintaining quality during transportation, often leading to suboptimal products reaching the market. To address this issue, a wireless transmission flexible ethylene monitoring device (WFEMD) was developed. This device comprises a flexible ethylene gas sensor and a signal transmission processing unit integrated with electronic components, enabling real-time monitoring capabilities. In this study, the catalytic activity of Pd and Pd/Ti heterojunctions was leveraged to enhance the ethylene gas sensing. The impact of Ti3C2Tx modified with varying masses of Pd nanoparticles on ethylene gas response levels was investigated. The signal transmission processing unit, fabricated by using the laser direct-writing method, was optimized to collect signals from the flexible ethylene gas sensor, convert them into corresponding ethylene concentrations, and transmit data via an antenna. By introducing a random forest (RF) classification algorithm, a remarkable 97.5% accuracy in predicting kiwifruit ripeness grades was achieved. The algorithm facilitated precise classification by collecting key parameters such as ethylene and CO2 during transportation. The WFEMD enables real-time acquisition of kiwifruit ethylene gas information, which is transmitted wirelessly for data visualization and traceability via mobile terminals. This empowers managers with timely insights into ethylene emissions and ripeness predictions, facilitating informed decision-making processes.